The Changing Role of Export Credit Agencies. (Washington, D.C. : International Monetary Fund, 1999)
Export credit agencies play an important role in international trade and investment flows. Exports insured or financed by the approximately 50 export credit agencies that are members of the Berne Union account for about 10 percent of their countries exports, which, in turn, represent about 78 percent of world exports. The IMF estimates that in 1997 debts to Berne Union members accounted for more than 21 percent of the total indebtedness of developing countries and economies in transition. Edited by Malcolm Stephens, this book provides useful background information to those whose involvement in international trade and investment brings them into contact with the services of export credit agencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet